농촌 여성들의 ALAD 유전형질별 철분영양상태와 철분제 섭취에 따른 영양상태의 변화 - 김희선(Hee Seon Kim); 김민경(Min Kyung Kim); 김소희(So Hee Kim); 이성수(Sung Soo Lee); 이병국(Byung Kook Lee) (Korean journal of community nutrition, 2006)
Previous studies have suggested that delta-aminolevulinic acid dehydratase (ALAD) phenotype differently affect mineral metabolism. The objective of this study was to determine the effectiveness of 6-month iron supplementation as syrup of NaFeEDTA in improvement of iron status according to ALAD genotype. One hundred thirty adult women living in rural areas of Asan were provided NaFeEDTA syrup once a week for 6 months at the dose of 64mg Fe/week. Three hundred control subjects were observed during the study period. Fasting blood was obtained for analyzing hemoglobin (Hb) and zinc protophorphyrin (ZPP) and serum was analyzed for ferritin, iron and total iron capacity (TIBC) levels before and after iron supplementation. Ninety percent of ALAD 1-1 (ALAD1) and 10% of ALAD 1-2 (ALAD2) genotype were observed in the control group. However in the intervention group, 98% showed ALAD1 while only 2% was ALAD2, which is significantly lower proportions of ALAD2 compared to the control group (p<0.01). The iron status of Intervention group significantly improved except for ferritin and TIBC regardless or ALAD genotype, while the control group did not show any changes in iron status except for ZPP. ZPP concentration of the control group significantly increased in both ALAD1 and 2 while the intervention group showed significantly decreased ZPP after supplementation in ALAD1. Iron supplementation in the form of NaFeEDTA seems to be effective in reduction of ZPP levels although ALAD2 did not show significant changes due to the small number. However, it is difficult to make a conclusion from these results, and more specified further investigation is needed with more participants.